Analisis Dampak Strategi Pengembangan Sumber Daya Manusia terhadap Peningkatan Kinerja UMKM - Fajaruddin Pakpahan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of human resource (HR) development strategies on improving the performance of Micro, Small, and Medium Enterprises (MSMEs). The strategies studied include skills training, marketing digitalization, and cross-sector collaboration and partnerships. The research method used is Systematic Literature Review with a content analysis approach to scientific literature published in the last five years. The results show that the strategy has a positive impact on increasing the competence of MSME actors, expanding markets, and strengthening competitiveness. However, several challenges such as the lack of digital literacy and limited training are still significant obstacles. Therefore, integrated policies, expanded access to training, and digital ecosystem support are needed to support the sustainable growth of MSMEs.